The hagiographer and the avatar: the life and works of Narayan Kasturi - Rigopoulos, Antonio (SUNY series in religious studies, 2021)
Introduction : Narayan Kasturi's hagiographical enterprise -- Narayan Kasturi's first life : investigating the hagiographer's roots -- Narayan Kasturi's magnum opus : Sathyam Sivam Sundaram, parts 1 & 2 -- Narayan Kasturi's magnum opus : Sathyam Sivam Sundaram, parts 3 & 4 -- The hagiographer's multiple roles within the Sathya Sai Baba movement -- A conversation with Professor Kasturi -- Understanding Sathya Sai Baba in the light of Dattātreya -- Narayan Kasturi's last years -- Epilogue : Narayan Kasturi's legacy lives on.